Rare earth-polyacid-based compound and preparation method and application thereof

By designing and synthesizing rare earth-polyacid-based organic-inorganic hybrid compound [Dy(DMF)8][PMo12O40], the problem of low electrocatalytic nitrite reduction activity and poor selectivity in the prior art is solved, and the stable existence of rare earth-polyacid-based compounds and excellent electrocatalytic properties are achieved, and the efficient detection and reduction of nitrites are used.

CN119874560AActive Publication Date: 2025-04-25NANTONG UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510063838.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-25
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The prior art has low activity and poor selectivity in electrocatalyzed nitrite reduction to synthesize ammonia, and there are difficulties in designing and synthesizing rare earth-polyacid-based compounds.

Method used

The rare earth-polyacid-based organic-inorganic hybrid compound [Dy(DMF)8][PMo12O40] is used to form a stable rare earth-polyacid-based compound through a specific preparation method, and the detection and reduction of nitrite is used for its excellent electrocatalytic properties.

Benefits of technology

The stable existence of rare earth-polyacid-based compounds and excellent electrocatalytic properties are achieved, and the nitrites can be detected and reduced efficiently, which improves catalytic activity and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874560A_ABST
    Figure CN119874560A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of synthesis of functional crystalline compounds, and discloses a rare earth-polyacid-based compound as well as a preparation method and application thereof. The chemical formula of the rare earth-polyoxometalate compound is [Dy (DMF) 8] [PMo12O40], and the cell parameter is # imgabs0 #. The preparation method comprises the following steps: sequentially adding an H3 [PMo12O40] solution as a lower solution, an organic solvent as a middle buffer layer solution and a mixed solution of Dy (NO3) 3.6 H2O and 4-hydroxyazobenzene-2-carboxylic acid as an upper solution C into a container, keeping a layered state, standing until crystal particles appear on the middle layer of the container, and drying to obtain the rare earth-polyoxometalate compound. The crystal particles are the rare earth-polyacid group compound. The material has excellent electro-catalysis characteristics and can be applied to detection and oxidation reduction of nitrite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of synthesis of functional crystalline compounds, and in particular relates to a rare earth-polyacid-based compound and a preparation method and application thereof. Background Art

[0002] Nitrite is not only harmful to human health, but also a major water pollutant. Electrocatalytic nitrite (NO2 ̄) reduction is not only beneficial to reduce the pollution of nitrite to the environment, but also can synthesize a chemical with high utilization value - ammonia (NH3). However, nitrite reduction is a complex process involving the transfer of multiple electrons and protons. Its reaction path is: *NO2→*NO→*N→*NH→*NH2→*NH3, where the N=O chemical bond energy is large (236kJ / mol), making it difficult for the *NO intermediate to dissociate. The complex reaction process and the large dissociation energy of the intermediates lead to low activity and poor selectivity of electrocatalytic nitrite reduction to synthesize ammonia. It is very challenging to develop a catalytic system for highly selective nitrite reduction to synthesize ammonia.

[0003] Polyoxometalates (polyacids for short) have reversible redox properties and strong electron acceptance and transfer capabilities, making them ideal candidate materials for supercapacitors and electrocatalysts. Rare earth metals have high coordination numbers and oxygen affinity, and can coordinate with oxygen atoms in polyacids. The introduction of rare earth ions changes the spatial arrangement of polyacid anions and changes the Bronste alkalinity of polyacid ions, thereby improving catalytic activity. At the same time, after the two are coordinated, the redox sites of rare earth elements can be changed, thereby changing the catalytic activity. However, due to the easy hydrolysis of rare earth ions themselves and the strong reactivity between rare earth ions and polyacids, which leads to easy precipitation and difficult crystallization, coupled with the coordination competition relationship between different metal ions and polyacids, the design and synthesis of rare earth-polyacid-based compounds are somewhat difficult. Therefore, the design and synthesis of rare earth-polyacid-based compounds is also a huge challenge. Summary of the invention

[0004] The purpose of the present invention is to at least partially solve the above-mentioned technical problems, and to provide a rare earth-polyacid-based organic-inorganic hybrid compound and its preparation method and application, which has excellent electrocatalytic properties and can be used for the detection and reduction of nitrite.

[0005] In a first aspect of the present invention, a rare earth-polyacid-based compound is provided, wherein the chemical formula of the rare earth-polyacid-based compound is [Dy(DMF)8][PMo 12 O 40 ], the unit cell parameters are:

[0006] In a second aspect of the present invention, a method for preparing the above-mentioned rare earth-polyacid-based compound is provided, wherein the preparation method comprises: adding a lower layer solution A, an intermediate buffer layer solution B, and an upper layer solution C to a container in sequence, maintaining the layered state, and standing until crystal particles appear in the intermediate layer of the container, wherein the crystal particles are rare earth-polyacid-based organic-inorganic hybrid compounds [Dy(DMF)8][PMo 12 O 40 ]; the lower layer solution A is H3[PMo 12 O 40 ] solution; the intermediate buffer layer solution B is an organic solvent; the upper layer solution C is a mixed solution of Dy(NO3)3·6H2O and 4-hydroxyazobenzene-2-carboxylic acid.

[0007] In some embodiments of the present invention, the preparation method of the lower layer solution A is: 12 O 40 ] is dissolved in a mixed solution of N,N-dimethylformamide and ethylene glycol.

[0008] In some embodiments of the present invention, H3[PMo 12 O 40 ] and the mixed solution of N,N-dimethylformamide and ethylene glycol are used in a ratio of (0.1-0.3) g: (5-15) mL.

[0009] In some embodiments of the present invention, in the mixed solution of N,N-dimethylformamide and ethylene glycol, the volume ratio of N,N-dimethylformamide to ethylene glycol is 1:3.

[0010] In some embodiments of the present invention, the intermediate buffer layer solution B is a mixture of N,N-dimethylformamide and ethylene glycol.

[0011] In some embodiments of the present invention, in the intermediate buffer layer solution B, the volume ratio of N,N-dimethylformamide to ethylene glycol is 1:1.

[0012] In some embodiments of the present invention, the preparation method of the upper solution C is: dissolving Dy(NO3)3·6H2O in DMF, adding 4-hydroxyazobenzene-2-carboxylic acid, and stirring at room temperature for 20-40 minutes to form an orange-red upper solution C.

[0013] In some embodiments of the present invention, the usage ratio of Dy(NO3)3·6H2O, 4-hydroxyazobenzene-2-carboxylic acid and DMF is 0.18 g:(0-0.30) g:8 ml.

[0014] In some embodiments of the present invention, H3[PMo 12 O 40The mass ratio of ] to Dy(NO3)3·6H2O is 1:1.

[0015] The third aspect of the present invention provides a use of the above-mentioned rare earth-polyacid-based compound or the rare earth-polyacid-based compound prepared by the above-mentioned preparation method in the detection of nitrite or the electrocatalytic reduction of nitrite.

[0016] In some embodiments of the present invention, the nitrite is potassium nitrite or sodium nitrite.

[0017] The fourth aspect of the present invention provides a method for electrocatalytic reduction of sodium nitrite, which comprises: preparing the above-mentioned rare earth-polyacid-based compound or the rare earth-polyacid-based compound prepared by the above-mentioned preparation method into a carbon paste electrode, using the carbon paste electrode as the working electrode, the Ag / AgCl electrode as the reference electrode, and the platinum electrode as the counter electrode to form a three-electrode system, and placing the three-electrode system in a sulfuric acid solution containing NaNO2 to carry out an electrocatalytic reduction reaction.

[0018] The rare earth-polyacid-based compound and the preparation method and application thereof according to the embodiments of the present invention have at least one of the following advantages:

[0019] (1) Rare earth elements have unique 4f electronic structures and chemical properties. Rare earth ion doping increases the number of surface active sites and improves charge transfer, thereby effectively regulating the electronic structure and electrocatalytic performance of the catalyst. This patent uses the easily hydrolyzed rare earth ion Dy 3+ It coordinates with N,N-dimethylformamide to form a stable complex, thereby allowing the rare earth ions to exist stably in the polyacid system.

[0020] (2) The rare earth complex binds to the polyacid PMo through electrostatic attraction 12 A stable structure is formed, which is constructed into a 3D supramolecular structure based on a large number of hydrogen bonds. The rich hydrogen bond network promotes reversible electron and proton transfer, thereby improving the electrocatalytic efficiency.

[0021] (3) The rare earth-polyacid-based compound prepared by the present invention has excellent electrocatalytic properties and can be applied to the detection and redox of nitrite.

[0022] (4) The preparation method provided by the present invention is simple and easy to promote in the industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] These and / or other aspects and advantages of the present invention will become apparent and readily understood from the following description of the preferred embodiments in conjunction with the accompanying drawings, in which:

[0024] Figure 1 The rare earth-polyacid compound [Dy(DMF)8][PMo 12 O40 ] molecular structure diagram;

[0025] Figure 2 The rare earth-polyacid compound [Dy(DMF)8][PMo 12 O 40 ] 3D supramolecular structure observed along the c-axis;

[0026] Figure 3 The rare earth-polyacid compound [Dy(DMF)8][PMo 12 O 40 ]’s infrared spectrum;

[0027] Figure 4 The rare earth-polyacid compound [Dy(DMF)8][PMo 12 O 40 ]’s UV spectrum;

[0028] Figure 5 Cyclic voltammograms at different scan rates in Test Example 2;

[0029] Figure 6 The rare earth-polyacid compound [Dy(DMF)8][PMo 12 O 40 ]Cyclic voltammograms of electrocatalytic decomposition of NaNO2 solutions with different concentrations. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further specifically described below by examples and in conjunction with the accompanying drawings. In the specification, the same or similar reference numerals indicate the same or similar components. The following description of the embodiments of the present invention with reference to the accompanying drawings is intended to explain the overall inventive concept of the present invention and should not be construed as a limitation of the present invention.

[0031] H3[PMo 12 O 40 ] was prepared by the following method:

[0032] 1. Weigh 10.5 g Na2MoO4·2H2O and dissolve it in 21 mL distilled water. Stir until completely dissolved. Add 1 mL concentrated H3PO4 and then 10 mL concentrated HCl and stir for 40 min.

[0033] 2. Transfer the solution to a 250mL separatory funnel, take 15mL of ether and shake manually for 30min until the solution is completely mixed. Cool and let stand for 20min. Separate the solution into layers and take out the lower layer.

[0034] 3. Add 10 mL of distilled water to the lower layer solution obtained in step 2, shake for 3 min, then add 8 mL of ether, shake for 30 min, let stand, separate the solution into layers, and separate the lower layer.

[0035] 4. Add 2 mL of distilled water to the lower solution obtained in step 3. A blue color appears in the solution. Slowly add concentrated HNO3 until it turns yellow. Place in a water bath at 80°C for 30 min. A large amount of yellow solid is produced. Separate and dry to obtain the pure product H3[PMo 12 O 40 ].

[0036] Example 1

[0037] Step 1: 0.05 g of H3[PMo 12 O 40 ] was dissolved in 8 mL of a mixed solution of N,N-dimethylformamide and ethylene glycol (V:V = 1:3) to form a clear light yellow solution A, which was used as the lower layer of the test tube;

[0038] Step 2: prepare 3 mL of a mixed solution B of N,N-dimethylformamide and ethylene glycol (V:V=1:1) as the intermediate buffer layer;

[0039] Step 3: Dissolve 0.18 g of Dy(NO3)3·6H2O in 8 ml of N,N-dimethylformamide, add 0.24 g of 4-hydroxyazobenzene-2-carboxylic acid, and stir at room temperature for 30 min to form an orange-red solution C as the upper layer;

[0040] Step 4: Place solutions A, B, and C into a test tube as the lower, middle, and upper layers, respectively. Let stand for 24 hours until crystal particles appear in the middle layer of the test tube.

[0041] Example 2

[0042] Step 1: 0.18 g of H3[PMo 12 O 40 ] was dissolved in 8 mL of a mixed solution of N,N-dimethylformamide and ethylene glycol (V:V = 1:3) to form a clear light yellow solution A, which was used as the lower layer of the test tube;

[0043] Step 2: prepare 3 mL of a mixed solution B of N,N-dimethylformamide and ethylene glycol (V:V=1:1) as the intermediate buffer layer;

[0044] Step 3: Dissolve 0.18 g of Dy(NO3)3·6H2O in 8 ml of N,N-dimethylformamide, add 0.24 g of 4-hydroxyazobenzene-2-carboxylic acid, and stir at room temperature for 30 min to form an orange-red solution C as the upper layer;

[0045] Step 4: Place solutions A, B, and C into a test tube as the lower, middle, and upper layers in sequence, and let stand for 24 hours. Crystal particles will appear in the middle layer of the test tube.

[0046] Example 3

[0047] Step 1: 0.18 g of H3[PMo 12 O 40 ] was dissolved in 8 mL of a mixed solution of N,N-dimethylformamide and ethylene glycol (V:V = 1:3) to form a clear light yellow solution A, which was used as the lower layer of the test tube;

[0048] Step 2: prepare 3 mL of a mixed solution B of N,N-dimethylformamide and ethylene glycol (V:V=1:1) as the intermediate buffer layer;

[0049] Step 3: Dissolve 0.18 g of Dy(NO3)3·6H2O in 8 ml of N,N-dimethylformamide and stir at room temperature for 30 min to form an orange-red solution C as the upper layer;

[0050] Step 4: Place solutions A, B, and C into a test tube as the lower, middle, and upper layers, respectively. Let stand for 24 hours until a precipitate appears in the middle layer of the test tube.

[0051] Examples 1 and 2 are different H3[PMo 12 O 40 ] The effect of quality on the reaction. Both Examples 1 and 2 can obtain crystals, but the crystals in Example 1 grow poorly. This may be due to the low concentration of polyacid and the inappropriate ratio when reacting with rare earth ions, resulting in poor crystal quality. In Example 3, 4-hydroxyazobenzene-2-carboxylic acid was not added, and no compound was obtained, only precipitation, indicating that 4-hydroxyazobenzene-2-carboxylic acid is very important for the synthesis.

[0052] Test Example 1

[0053] High-quality single crystals were selected from the crystals prepared in Example 2 for structure determination, as follows:

[0054] The single crystals were tested and all diffraction data were collected using a Bruker APEX-IICCD at 296 K and a Bruker D8VENTURE PHOTONII single crystal diffractometer at 150 K. The radiation source was Mo Kα radiation from a graphite monochromator. The coordinates of hydrogen atoms on the water molecule were obtained by the difference Fourier synthesis method, and the coordinates of all non-hydrogen atoms were obtained by the direct method and optimized by anisotropic thermal parameter correction and matrix least squares method. The hydrogen atoms were directly added to the molecular formula. The crystallographic data and structural parameters are shown in Table 1. The compound structure diagram and 3D supramolecular structure diagram are shown in Table 1. Figure 1 and 2shown.

[0055] The infrared and ultraviolet spectra of the compound are shown in Figure 3 and Figure 4 In the infrared spectrum of the compound, it appears in the range of 1200-1800cm -1 The peaks in the wavenumber range are attributed to the characteristic vibration peaks of the ligand DMF. It is also found that the characteristic vibration peak of the C=O bond has red-shifted from 1678 cm -1 (free DMF molecules) shifted to 1654 cm -1 The compound showed four characteristic peaks of Keggin structure, which are 1061, 956, 877 and 803 cm-1. –1 , which are respectively classified as PO a Stretching vibration of Mo-O bond d The stretching vibration of Mo-O c Stretching vibration of Mo-O d The stretching vibration peak of O a , O d , O b and O c They represent the bridging oxygen in the Keggin structure, at the end, between different groups of MoO6 octahedrons, and between the same group. -1 The peak at 3000 cm-1 is attributed to intermolecular hydrogen bonding. -1 The absorption bands on the left and right belong to the -CH stretching vibration of the methyl group on the DMF molecule.

[0056] Table 1

[0057]

[0058] Test Example 2

[0059] Weigh 0.01 g of rare earth-polyacid compound [Dy(DMF)8][PMo 12 O 40 ], 0.10g of graphite was placed in an agate mortar and ground for 30min to make it fully mixed, 1mL of liquid paraffin was dropped into it, stirred evenly and then packaged in a polytetrafluoroethylene tube with an inner diameter of 3mm and a length of 5cm containing a copper rod, gently compacted and the surface polished to make a carbon paste electrode of the compound.

[0060] A three-electrode system was formed using a carbon paste electrode as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum electrode as the counter electrode. Cyclic voltammograms were obtained at different scan rates (0.01, 0.02, 0.04, 0.06, 0.08, 0.10, and 0.15 V / s) in a 0.1 mol / L H2SO4 solution within a potential range of 1.6 to -0.6 V. The following table shows the cyclic voltammograms: Figure 5 As shown. Figure 5 It can be seen that with the increase of scanning rate, the symmetry of the image is good, indicating that its electrocatalytic reversibility is good.

[0061] A three-electrode system was formed with a carbon paste electrode as the working electrode, an Ag / AgCl electrode as the reference electrode, and a platinum electrode as the counter electrode. The three-electrode system was placed in 0.1mol / L H2SO4 containing different concentrations of NaNO2. At a scan rate of 0.20V / s, electrocatalytic tests were performed on NaNO2 with concentrations of 2mmol / L, 4mmol / L, 8mmol / L, 16mmol / L, and 32mmol / L, and the cyclic voltammograms are shown in the figure below. Figure 6 As shown in Figure 2, with the increase of NaNO2 solution concentration, all reduction peak currents increased, while the corresponding oxidation peak currents decreased significantly, indicating that the rare earth-polyacid compound [Dy(DMF)8][PMo 12 O 40 ] has electrocatalytic activity towards NaNO2.

[0062] The rare earth-polyacid-based compound and the preparation method and application thereof according to the embodiments of the present invention have at least one of the following advantages:

[0063] (1) Rare earth elements have unique 4f electronic structures and chemical properties. Rare earth ion doping increases the number of surface active sites and improves charge transfer, thereby effectively regulating the electronic structure and electrocatalytic performance of the catalyst. This patent uses the easily hydrolyzed rare earth ion Dy 3+ It coordinates with N,N-dimethylformamide to form a stable complex, thereby allowing the rare earth ions to exist stably in the polyacid system.

[0064] (2) The rare earth complex binds to the polyacid PMo through electrostatic attraction 12 A stable structure is formed, which is constructed into a 3D supramolecular structure based on a large number of hydrogen bonds. The rich hydrogen bond network promotes reversible electron and proton transfer, thereby improving the electrocatalytic efficiency.

[0065] (3) The rare earth-polyacid-based compound prepared by the present invention has excellent electrocatalytic properties and can be applied to the detection and redox of sodium nitrite.

[0066] (4) The preparation method provided by the present invention is simple and easy to promote in the industry.

Claims

1. A rare earth-polyacid compound, characterized in that: The chemical formula of the rare earth-polyacid compound is [Dy(DMF)8][PMo 12 O 40 ], the unit cell parameters are:

2. A method for preparing the rare earth-polyacid compound according to claim 1, characterized in that: The preparation method comprises: adding a lower layer solution A, an intermediate buffer layer solution B, and an upper layer solution C into a container in sequence, maintaining the layered state, and standing until crystal particles appear in the intermediate layer of the container, wherein the crystal particles are rare earth-polyacid-based organic-inorganic hybrid compounds [Dy(DMF)8][PMo 12 O 40 ]; The lower solution A is H3[PMo 12 O 40 ] solution; The intermediate buffer layer solution B is an organic solvent; The upper layer solution C is a mixed solution of Dy(NO3)3·6H2O and 4-hydroxyazobenzene-2-carboxylic acid.

3. The preparation method according to claim 2, characterized in that: The preparation method of the lower layer solution A is: 12 O 40 ] is dissolved in a mixed solution of N,N-dimethylformamide and ethylene glycol.

4. The preparation method according to claim 3, characterized in that: H3[PMo 12 O 40 ] and the mixed solution of N,N-dimethylformamide and ethylene glycol are used in a ratio of (0.1-0.3) g: (5-15) mL.

5. The preparation method according to claim 2, characterized in that: The intermediate buffer layer solution B is a mixture of N,N-dimethylformamide and ethylene glycol.

6. The preparation method according to claim 2, characterized in that: The preparation method of the upper layer solution C is as follows: dissolving Dy(NO3)3·6H2O in DMF, adding 4-hydroxyazobenzene-2-carboxylic acid, and stirring at room temperature for 20-40 minutes to form an orange-red upper layer solution C.

7. The preparation method according to claim 6, characterized in that: The usage ratio of Dy(NO3)3·6H2O, 4-hydroxyazobenzene-2-carboxylic acid and DMF is 0.18g:(0~0.30)g:8ml.

8. The preparation method according to claim 7, characterized in that: H3[PMo 12 O 40 The mass ratio of ] to Dy(NO3)3·6H2O is 1:

1.

9. Use of the rare earth-polyacid compound according to claim 1 or the rare earth-polyacid compound prepared by the preparation method according to any one of claims 2 to 8 in detecting nitrite or electrocatalytic reduction of nitrite.

10. A method for electrocatalytic reduction of sodium nitrite, characterized in that: The method comprises: preparing a carbon paste electrode from the rare earth-polyacid compound described in claim 1 or the rare earth-polyacid compound prepared by the preparation method of any one of claims 2 to 8, using the carbon paste electrode as a working electrode, an Ag / AgCl electrode as a reference electrode, and a platinum electrode as a counter electrode to form a three-electrode system, and placing the three-electrode system in a sulfuric acid solution containing nitrite to carry out an electrocatalytic reduction reaction.

Citation Information

Patent Citations

  • 4,4'-bis(imidazolyl)biphenyl modified Keggin type polyacid as well as preparation method and application thereof

    CN108383860A

  • Rare earth complex heteropolyacid salt, preparation method thereof and application of rare earth complex heteropolyacid salt in cellulose cracking

    CN115028605A

  • Preparation and application of polyoxometalate complex constructed by reductive phosphomolybdic polyacid {P4Mo6}

    CN117263994A

  • Arsenic molybdate-based rare earth derivative and preparation method thereof, modified compound of arsenic molybdate-based rare earth derivative and preparation method thereof, modified electrode and application thereof

    CN118852017A